Investigating the functions of discourse markers in Malaysian english blogs - Nur Sarah Baharudin (Kulliyyah Of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The purpose of this thesis is to analyse the distribution and functions of discourse markers in forty-eight Malaysian English blogs from January to August 2010, from the socio-pragmatic standpoint, using both Halliday's (1994) Systemic Functional Linguistics (SFL) and Gonzalez's (2004) Pragmatic Functions frameworks. Gonzalez's (2004) framework was chosen as it differentiates nine different pragmatic functions accordingly (i.e. reformulate, sequential, addition, concluding, commentary, delays, emphasizer, recover and topic shifter), while Halliday's (1999) framework comprises three broad areas, which are the ideational, interpersonal and textual metafunctions. Blogs were chosen as the units of analysis because it is a form of online interaction that is informal between users who may or may not know each other, but the interaction resembles everyday spoken discourse, which would entail the use of discourse markers. Data was collected through a non-interventional method and analysed using content analysis followed by descriptive statistics. The study found a total of thirteen discourse markers (i.e. and, but, so, because, then, well, anyway, okay, like, I think and I mean, you know and yeah) with three hundred and sixty-nine occurrences. Markers and and but are found to be the most used markers with one hundred and sixty-two and eighty occurrences, respectively. Moreover, each marker exhibited diverse functions according to the context. It is revealed that the discourse marker and had five diverse functions. Discourse markers but, so and then followed in second place with four functions each. Because and well constituted three functions while anyway, like, I think and I mean come with two each. Finally, discourse markers okay and you know constitute one function each. An overview of the central themes in the selected blog posts also addressed the distinctive characteristics between genders, particularly in their writing styles. The analysis revealed that female bloggers preferred discourse markers and and then, which demonstrate a better narrative skills and the ability to maintain the floor while male bloggers favoured discourse markers so and well, which indicate closure of a topic. The limitations of the study as well as suggestions for future research are offered in the conclusion of the thesis.